Analisis Keterampilan Mengadakan Variasi dalam Meningkatkan Efektivitas Pembelajaran pada Anak Usia Dini - Junita Ningsih; Kholidah Nur; Nur Fadilah; Riski Hidayah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study analyzes variation skills as a strategy to improve the effectiveness of learning in early childhood. Early childhood has unique characteristics, such as short attention span and high curiosity, so variation in learning is essential to maintain their interest and engagement. Variation includes the use of various methods, media, teaching styles, and activities, which are adjusted to the developmental needs of children. Through a qualitative approach based on literature studies, this study found that variation in learning can improve children's learning motivation, concentration, and social and emotional skills. Variation also supports multisensory-based learning that strengthens conceptual understanding. The conclusion of this study emphasizes the importance of training for teachers to master variation skills in learning, in order to create meaningful and enjoyable learning experiences for early childhood.